MR Imaging and Proton MR Spectroscopy in Adult Krabbe Disease - Farina, Laura (AJNR Am J Neuroradiol, 2000)
Summary: We present the MR imaging findings in four patients (two pairs of siblings from two unrelated families) with adult Krabbe disease. In the first family, clinical presentation mimicked familial spastic paraplegia. Their MR images showed selective, increased signal intensity on T2-weighted sequences along the corticospinal tracts, most prominently in the proband and barely detectable in her brother. Proton MR spectroscopy showed increased choline and myo-inositol in the affected white matter. In the second family, the clinical presentation differed in that the signs of pyramidal tract involvement were asymmetrical, with concomitant asymmetry on MR images in one. In adults, Krabbe disease may present on MR imaging with selective pyramidal fiber involvement.